(untitled) (Research, Society and Development, 2024)
The international press recently reported floods in the southern Brazil, specifically in the state of Rio Grande do Sul (RS), during May 2024. These floods caused significant economic losses, affecting the agriculture, industry, and commerce sectors, and displacing thousands of people who lost their homes. A total of 540,188 families were displaced, as 471 of the 497 cities in the state were affected by the storms - equivalent to 94.77% of the total. In addition, floods also provide new breeding grounds for mosquitoes, which consequently increases outbreaks for Dengue virus. This arbovirus causes one of the most human concerning arthropod-borne diseases globally. This work presents an analysis of the Dengue situation in the state of Rio Grande do Sul, and lists the cases of this disease after the floods in the city of Porto Alegre, combining official data, meteorological information and scientific knowledge on the subject. In 2023 1,649,144 Dengue infection were reported, with 1,179 deaths. Comparatively, in 2024, the numbers reached to 6,148,161 with 4,207 deaths by the 25rd week, i.e., by the end of June. In this context, the RS has a 12.66% fatality rate for severe cases, the second highest in the country. Thus, it is crucial to prepare health systems for proper screening and follow-up of potential future patients resulting from the floods. Prevention campaigns and efforts to combat the spread of the Ae. aegypti mosquito urgently need to be mobilized through various communication channels by the government, reaching households, with priority given to those located in high-risk areas, especially the recently flooded regions.